The effects of extensive reading on language proficiency and motivation to read on fourteen year old students in malaysia - Kaur, Navinder; Awang, Zubaidah; Abdullah, Khairi Izwan (2008)
This research was carried out to investigate the effects of extensive reading on language proficiency and motivation to read on fourteen year old students in a premier school in Malaysia. There were 120 participants who were divided into monitored and unmonitored groups. The monitored group was engaged in a weekly scheduled time to do extensive reading by reading single page articles in school while the unmonitored group read single page articles whenever they were free. Results revealed that the monitored group scored significantly higher in comprehension, cloze and vocabulary tests than the unmonitored group after 9 months of treatment. However, there was no significant difference in the affective questionnaire which measured motivation to read for the groups. The results suggest that proper management of extensive reading should be part of the curriculum where teachers and students play a crucial role in improving students’ language proficiency. There seems to be a need for a shift in schools towards a reading pedagogy that appreciates the spirit of the ER approach with its focus on reading for pleasure and information.